WORKSHOP PERFORMANCE ART UNTUK SISWA SMKN 9 SURAKARTA - Santoso Haryono (Abdi Seni, 2016)
The training in performance art workshop is held remembering that students in SMK 9 Surakarta have had the basic understanding in visual arts adequately. Students of general Senior High School (SMA) in Surakarta don’t have the aspect. This devotion is executed in the form of performance art Workshop. The technique uses a model of studying with. The model is used in order that students are able to recieve the workshop material and are hoped to be able to bring creative ideas. Key words : workshop, performance art.